Proton magnetic resonance spectroscopy may predict future brain lesions in SLE patients: a functional multi-imaging approach and follow up. Issue 7 (7th January 2005) - Castellino, G; Govoni, M; Padovan, M; Colamussi, P; Borrelli, M; Trotta, F
Abstract : Objective: To determine whether single photon emission tomography (SPECT) and magnetic resonance spectroscopy ( 1 H-MRS) can predict the appearance of new lesions in systemic lupus erythematosus (SLE), detectable by magnetic resonance imaging (MRI). Methods: 99 Tc m -HMPAO-SPECT, brain MRI, and 1 H-MRS were done in eight women with SLE (mean age 31.8 years; disease duration 5.5 years). NAA/Cho, NAA/Cre, and Cho/Cre ratios were assessed in hypoperfused and normoperfused areas detected by SPECT that were normal on MRI examination. Reference values were obtained in 20 normal healthy controls. In five patients, MRI was repeated four to six years after the first evaluation. Results: Mean NAA/Cho and Cho/Cre ratios in hypoperfused and normoperfused frontal areas were, respectively, lower and higher than control. There were no differences in NAA/Cre ratios. Mean Cho/Cre ratios were increased in hypoperfused v normoperfused brain areas (mean (SD): 1.43 (0.27) v 1.00 (0.07); p<0.023). NAA/Cre ratios were not altered (2.18 (0.30) v 1.99 (0.28); p = 0.381). Three of five patients who had a second MRI had new lesions in areas previously abnormal on MRS and SPECT but normal on first MRI. One patient with positive MRI, SPECT, and MRS showed an increase in the number of MRI lesions; one patient with negative MRI, SPECT, and MRS did not show any new lesions. Conclusions: Abnormalities reflecting altered perfusion or neuronal-chemical changes can be demonstrated by functional imaging techniques even in the absence of morphological lesions detectable by MRI. The abnormal areas identified by SPECT and MRS may predict future parenchymal damage.